2011
DOI: 10.3989/mc.2011.62110
|View full text |Cite
|
Sign up to set email alerts
|

Características mecánicas de hormigones con áridos reciclados procedentes de los rechazos en prefabricación

Abstract: RESUMENLa necesidad de disminuir la cantidad final de residuos de construcción y demolición que se producen en las plantas de prefabricados de hormigón nos ha llevado a analizar el comportamiento mecánico de un hormigón elaborado con áridos reciclados procedentes de piezas prefabricadas de hormigón, con la finalidad de un posible futuro uso como árido en dosificaciones de hormigón armado y pretensado para piezas prefabricadas. Se ha trabajado con áridos reciclados en dos situaciones: estado natural y sometidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…Outro fator de dúvida é o desempenho do ARC em comparação com o natural. Na literatura [17,18,25,31], observa-se que o agregado reciclado, de forma geral, apresenta valores menores de massa específica em comparação com o agregado natural, além de altos índices de absorção e material pulverulento. Segundo SOARES et al [28], ainda não existe um consenso na literatura se a incorporação de ARC resulta na queda de desempenho mecânico do concreto.…”
Section: Introductionunclassified
“…Outro fator de dúvida é o desempenho do ARC em comparação com o natural. Na literatura [17,18,25,31], observa-se que o agregado reciclado, de forma geral, apresenta valores menores de massa específica em comparação com o agregado natural, além de altos índices de absorção e material pulverulento. Segundo SOARES et al [28], ainda não existe um consenso na literatura se a incorporação de ARC resulta na queda de desempenho mecânico do concreto.…”
Section: Introductionunclassified
“…Compressive strength decrease escalated when RCA replacement rate was increased because, by increasing the RCA replacement rate, compressive strengths of concretes were reduced due to RCA characteristics such as heterogeneity, porosity, high absorption and low strength [ 31 ]. At the age of 28 days, the compressive strength of C20-RCA30 decreased 11.25% while that of C20-RCA50 decreased 36.17%.…”
Section: Resultsmentioning
confidence: 99%
“…To recycle concrete waste into new building products, intensive research worldwide, demonstrating that in general, the use of recycled aggregates from concrete in new fabrication of concrete has resulted in enhanced improvement of mechanical properties [16][17][18][19]. Perez-Benedicto et al [20] studied the mechanical behavior of concrete made with recycled aggregate coming from discarded concrete prefabricated units, demonstrating that including coarse aggregate replacement can offer excellent quality for structural applications providing similar compressive strength respect conventional concrete. Cakir and Dilbas [21] demonstrated that durability of concrete can be increased up to 60% using recycled aggregate and an optimized ball mill method.…”
Section: Global Contextmentioning
confidence: 99%